Victims of crime acts in Slovakia (does it fulfil minimum European requirements?) - Kováčová, Zuzana (Актуальні проблеми правознавства, 2018)
The attempt to reduce the risk of secondary and repeat victimisation, of intimidation and of retaliation by the offender done in the article. As wide a range of measures as possible should be made available to practitioners to prevent distress to the victim during court proceedings in particular as a result of visual contact with the offender, his or her family, associates or members of the public.